Neoliberalism in the Gutter: Latin American Comics and Society since the 1990s - Mauricio Espinoza (Studies in 20th & 21st Century Literature, 2017)
Since the 1990s, Latin America has undergone important economic, social, political, and cultural transformations marked by the consolidation of neoliberal policies that swept through the region and helped define its contemporary societies. This essay explores comic books and cartoons produced by Latin American artists during this period, interrogating the various ways in which the graphic narrative medium has both reflected and reacted against neoliberalism’s impact throughout the continent. Through the use of political cartooning, superhero comics, and graphic novels that employ supernatural themes, the artists analyzed here have engaged with the big, contentious issues of contemporary Latin America, including foreign intervention, loss of national sovereignty, corrupt politicians, poverty, and violence.
Keywords: Latin America; comics; political cartooning; graphic novel; neoliberalism; parody; social protest; superheroes; science fiction; mutants